Role of insulin-like growth factor 1 in pathogenesis of acne vulgaris: relation to acne severity and body mass index - Adel, Shereen; Abd-El-Raheem, Talal A.; Ezzat, Ghada; Ismail, Nermeen M. (International Journal of Research in Dermatology, 2020)
Background: Acne vulgaris is a multifactorial skin disease. A potential role for insulin-like growth factor-1 (IGF-1) has been suggested in the pathogenesis of acne. Several studies have shown that elevated levels of serum IGF-1 correlate with overproduction of sebum and acne. Objective: Measurement of the serum level of IGF-1 in acne patients in comparison to normal controls and evaluating the relationship of these levels to severity of acne and body mass index (BMI), in order to investigate the role of this factor in the pathogenesis of acne. Methods: Fifty-four patients with acne vulagaris and 42 healthy controls were included. History taking, dermatological examination, clinical assessments of acne severity, calculation of BMI were performed for patients. Blood samples were collected from all participants for estimation of serum IGF-1 level using enzyme linked immunosorbant assay. Results: There was a significantly higher serum IGF-1 level in acne patients (p<0.05) than controls. Authors didn’t find a relation of significance between elevated serum IGF-1 level and degree of acne severity and BMI (p>0.05). There was a significant positive correlation between serum IGF-1 level and age of the patients. Conclusions: There is a significantly higher serum IGF-1 in acne patients than controls not related to acne severity and BMI. That is adding to the scientific evidence of IGF-1 role in pathogenesis of acne vulgaris.